Classes of multiojectives games possessing Pareto equilibria - Laura Levaggi; Lucia Pusillo (Operations Research Perspectives, 2017)
In this paper we study non cooperative games with potential as introduced by Monderer and Shapley in 1996. We extend the notions of weighted and ordinal potential games to a multicriteria setting and study their Pareto equilibria. The importance of these games is the existence of Pareto equilibria in pure strategies and in the finite case and the approximate equilibria for some classes of infinite potential games. Some applications are studied via potential games: a water resource problem, a voluntary contribution model, peering games for telecommunication models.
Keywords: 330; Multicriteria games; Pareto equilibria; Weighted potential; Ordinal potential